2016
DOI: 10.1088/1009-0630/18/4/01
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polyimide Film by Dielectric Barrier Discharge at Atmospheric Pressure

Abstract: In this paper, polyimide (PI) films are modified using an atmospheric pressure plasma generated by a dielectric barrier discharge (DBD) in argon. Surface performance of PI film and its dependence on exposure time from 0 s to 300 s are investigated by dynamic water contact angle (WCA), field emission scanning electron microscopy (FESEM), and Fourier transform infrared spectroscopy in attenuated total multiple reflection mode (FTIR-ATR). The study demonstrates that dynamic WCA exhibits a minimum with 40 s plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Thus, water drops can spread rapidly on the surface, which makes an important contribution to the super hydrophilicity. [ 43,44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Thus, water drops can spread rapidly on the surface, which makes an important contribution to the super hydrophilicity. [ 43,44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the plasma treatment of polyimide films, the main attention has been devoted to the possibility to promote the adhesion between the plasma-treated polyimide surface and subsequently deposited metallic coating (e.g., copper [29][30][31][32][33][34]). Based on the reported results, it has been found that plasma treatment is indeed capable of inducing a substantial increase of surface energy of Kapton that in turn enhances the adhesive strengths of metallic films onto polyimide substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of early works employed low-pressure plasma treatment that is in many cases not compatible with the demand of a cheap and fast process [29][30][31]. Because of this, further studies were performed with atmospheric pressure plasmas generated in different gases and gas mixtures such as He/O 2 /NF 3 [32], Ar [33], N 2 /air [34]. It has been reported that the activation and hydrophilization of polyimide films may be achieved also in these cases in a relatively short period of time that ranged, depending on the operational condition, from several seconds up to several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the surface modification of PI films using excimer lasers, plasma treatment, and excimer UV lamp radiation have attracted the attention of researchers as a means to improve metal/polymer adhesion. 17 23 Each method has its own advantages, and using the excimer UV lamp has the benefit of being economical, convenient to use, and environment friendly.…”
Section: Introductionmentioning
confidence: 99%